2000
DOI: 10.1080/17450390009381941
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and thyroid hormone levels of growing rats in response to different dietary proteins ‐ soy protein or casein

Abstract: Energy balances were measured by indirect calorimetry in four experiments on male growing rats, fed restrictively on isoenergetic and isonitrogenous (10% CP) diets based on either casein supplemented with methionine, or soy protein isolate (experiments 1, 2 and 3) and soy protein isolate supplemented with methionine (experiment 0), respectively. At the end of experiments the rats were killed for body analysis and determination of thyroid hormones and lipids in blood as well as mitochondrial respiration in live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…This finding further confirms the role of the yeast Saccharomyces cerevisiae as an excellent system in which to study thyroid hormone receptor action [32]. Klein et al [25] reported that soy protein isolate had no effect on T 3 and free T 3 , but significantly decreased T 4 compared with casein in rats. The decrease in T 4 concentration may be responsible for the cholesterol-lowering effect of Saccharomyces cerevisiae, since T 3 is responsible for the maintenance of cholesterol homeostasis in the vascular endothelial lining [40,59].…”
Section: Carcass and Organ Weights Of Broiler Chickenssupporting
confidence: 71%
“…This finding further confirms the role of the yeast Saccharomyces cerevisiae as an excellent system in which to study thyroid hormone receptor action [32]. Klein et al [25] reported that soy protein isolate had no effect on T 3 and free T 3 , but significantly decreased T 4 compared with casein in rats. The decrease in T 4 concentration may be responsible for the cholesterol-lowering effect of Saccharomyces cerevisiae, since T 3 is responsible for the maintenance of cholesterol homeostasis in the vascular endothelial lining [40,59].…”
Section: Carcass and Organ Weights Of Broiler Chickenssupporting
confidence: 71%
“…In addition the higher excess of ME in SPI-, in comparison to CAS+, seems to be divided into both FER and HP. Analogous experiments with growing rats fed low protein diets based on SPI-or CAS+ (KLEIN et al, 2000) are not consistent with our findings of a similar energetic efficiency in SPI-and CAS+ fed pigs. The SPI-fed rats retained both less protein energy and fat energy in comparison to CAS-fed rats.…”
Section: Discussioncontrasting
confidence: 46%
“…1. development seemed to be closely related to changes in insulin, thyroid hormone (33), and glucose concentrations in blood (17,59). Another important point of these changes is that glucose uptake becomes insulin sensitive after 2 wk of life (23,28).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone has received wide attention as a possible trigger of developmental changes in infant rats, because its circulating concentration increases significantly during the second postnatal week (33,61,68).…”
Section: Discussionmentioning
confidence: 99%